PERAN PPNS SAT POL PP DALAM PENEGAKAN PERDA NO 8 TAHUN 2009 TENTANG PENGAWASAN DAN PENGENDALIAN MINUMAN BERALKOHOL DIKOTA SEMARANG - Aris Nursetyabudi; Dyah Listyarini; Arikha Saputra (Program Studi Ilmu Hukum Fakultas Hukum dan Ilmu Sosial Universitas Pendidikan Ganesha Singaraja, 2022)
The Civil Service Police Unit (Satpol-PP) is a government apparatus at the regional level which has the function to carry out Regional Regulations and Regional Head Regulations on the basis of Law 23 of 2014 concerning Regional Government. Then this was continued in Government Regulation Number 16 of 2018 concerning the Civil Service Police Unit. Therefore, considering the importance of the role of Satpol-PP in enforcing regional regulations, this 'research' aims to find out how the 'role of the police unit' civil service in Semarang City is in enforcing regional regulations No. 8 of 2009 concerning 'Supervision' and 'Control of alcoholic beverages. in the city of Semarang. The research method used is the normative juridical method with case studies on enforcement by the Civil Service Police Unit (Satpol-PP) in Semarang City whose data includes: data on cafes, restaurants, karaoke places and/or places where alcohol drinks do not meet the requirements as regulated in Regional Regulation No. 8 of 2009, there are still many restaurants that do not meet the requirements stipulated in the legislation. Therefore, the role played by the Civil Service Police Unit is by litigation, namely the enforcement process as stipulated in the Criminal Procedure Code and Administrative Sanctions in the form of administrative termination in the form of temporary suspension.